The Andalusian Tourism Sector during the Economic Crisis and its Impact on Regional Development - García-López, Ana Mª; Campoy-Muñoz, Mª del Pilar; Cardenete-Flores, M. Alejandro; Marchena-Gómez, Manuel J. (Revista de Estudios Andaluces, 2018)
It is not common practice to assess tourism’s effects on regional development, although its benefits for host economies are widely known. This paper attempts to discern such activity’s role in a geographic setting by applying structural analysis techniques based on social accounting matrices (SAMs). This methodological approach is applied to the case of Andalusia during the period 2010-2014, encompassing both the financial crisis period and the apparent resurgence. The research aims to reflect on the andalusian economy from the perspective of tourism and know its impacts on the regional territory. The proposed methodology is applied to a region where tourism became more prominent during the financial crisis. The results indicate that tourism’s significance in the host economy is due its own particular behaviour and also to the performance of other economic sectors during the study period. Tourism has shown considerable carry-over capacity in the territory, although challenges have arisen in employment, demand and technological density aspects. All of them should be addressed so that tourism can provide a sustainable support for regional development. Tourism sector’s appeared as a strategic sector, partly due to its specific performance, though also to the other sectors’ performance, either declining industries such as construction or with lighter presence, as in the case of industrial activities. Tourism has also shown itself to be a pro-cyclical sector, with landmarks. Yet the tourism sector has shown proven resilience and a considerable ability to foster economic development in the territory.